2021
DOI: 10.1108/f-03-2020-0031
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating campus interactions – critical success factors according to university facility directors

Abstract: Purpose The purpose of this paper is to investigate which critical success factors (CSFs) influence interaction on campuses as identified by the facility directors (FDs) of Dutch university campuses and to discuss how these compare with the literature. Design/methodology/approach All 13 Dutch university campus FDs were interviewed (office and walking interview), focussing on CSFs relating to spaces and services that facilitate interaction. Open coding and thematic analysis resulted in empirically driven cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…After indicating a location on the map, a pop-up followed asking to rate that location on a 7-point Likert scale for 20 spatial characteristics, based on the environmental descriptors as defined by Mehrabian and Russell [ 19 ]. Finally, respondents were also asked to indicate what 13 service variables contributed to these interactions, again on a 7-point Likert scale and based on the previous study mentioned above [ 18 ] (see Section 2.6 ). Participants were asked to answer all questions based on their experiences in 2019, to ensure the COVID-19 measures in place during the study would not influence the results.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…After indicating a location on the map, a pop-up followed asking to rate that location on a 7-point Likert scale for 20 spatial characteristics, based on the environmental descriptors as defined by Mehrabian and Russell [ 19 ]. Finally, respondents were also asked to indicate what 13 service variables contributed to these interactions, again on a 7-point Likert scale and based on the previous study mentioned above [ 18 ] (see Section 2.6 ). Participants were asked to answer all questions based on their experiences in 2019, to ensure the COVID-19 measures in place during the study would not influence the results.…”
Section: Methodsmentioning
confidence: 99%
“…For location and service variables, all variables were asked on a 7-point Likert scale, ranging from 1 (strongly disagree) to 7 (strongly agree) (see Table 2 ). These variables were selected based on Mehrabian and Russell [ 19 ] (for location variables) and a previous study by these authors [ 18 ] in which university facility directors identified key success factors for unplanned meetings (for service variables).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations